Analisis Campur Kode Bahasa Daerah Nias dalam Proses Pembelajaran di SMP Swasta Idanoi - Zebua, Anggi Mesrawati; Bate’e, Friska Sotania; Laia, Foster Helwin; Harefa, Noveri Amal Jaya (Indo-MathEdu Intellectuals Journal, 2024)
The research entitled "Analysis of Nias Regional Language Code Mixing in the Learning Process at Idanoi Private Junior High School" was conducted with the aim of finding out things related to code mixing that often occurs in the school environment in the delivery of information by students. The method used in this study is qualitative, using a descriptive approach in the form of written or spoken words from people and observed behavior. The data collection technique was produced from observations in the form of video recording documentation and audio recordings carried out at Idanoi Private Junior High School. The research was carried out in one meeting in which the researcher took a sample of 10 boys and 10 girls in class VII-A. After taking the sample, the researcher conducted a codemixing analysis and concluded when the teaching and learning process began. After conducting the research, the researcher learned that the code mixing that occurred in Idanoi Private Junior High School was influenced by several factors, including the community environment, social interactions, and the school environment itself